Antibacterial Silver Nanomaterial Synthesis From Mesoflavibacter zeaxanthinifaciens and Targeting Biofilm Formation - Oves, Mohammad; Rauf, Mohd Ahmar; Hussain, Afzal; Qari, Huda A.; Khan, Aftab Aslam Parwaz; Muhammad, Pir; Rehman, Md Tabish; Alajmi, Mohammad Fahad; Ismail, Iqbal I. M. (Frontiers in Pharmacology, 2019)
Considering the significance of biological and eco-friendly nanomaterials, in the present study, we have synthesized silver nanoparticles from the exopolysacchraide of recently recovered bacterial strain CEES51 from the Red Sea coastal area Jeddah, Saudi Arabia. 16S rRNA gene sequencing to characterize the isolated bacteria, and it was identified as Mesoflavibacter zeaxanthinifaciens and achieved an accession number MH707257.1 GenBank. The bacterial strain is an excellent exo-polysaccharide producer and survived at hyper-saline (30%) and high temperature (50 °C) conditions. The bacterial culture supernatant was employed for the production of silver nanoparticles at room temperature. UV-visible spectrophotometer optimized the synthesized nanoparticles, and their size was determined by Nanophox particle size analyzer and Dynamic light scattering (DLS). Additionally, the XRD and FTIR studies approved its crystalline nature and the involvement of organic functional groups in their formation. The synthesized nanomaterials were tested for their antibacterial and antibiofim properties against pathogenic microorganisms Bacillus subtilis and Methicillin-resistant Staphylococcus aureus (MRSA). The antimicrobial property showed time, and dose-dependent response with a maximum of zone inhibition was observed at around 22 mm and 18 mm at a dose of 50 µg/well against B. subtilis and, S. aureus respectively. Furthermore, the synthesized AgNPs possess a strong antibiofilm property, and the manufactured nanoparticles were also found to be biocompatible as depicted by RBC lysis assay and their interaction with HEK-293 cell lines. Therefore, Mesoflavibacter zeaxanthinifaciens is an excellent source for exopolysaccharide synthesis and assisted silver nanoparticle production. Bacterial-mediated exopolysaccharide might be exploited in the development of antimicrobial agents